Accelerated versus standard corneal collagen cross-linking in pediatric keratoconus patients: 24 months follow-up results. Issue 5 (October 2018) - Sarac, Ozge; Caglayan, Mehtap; Uysal, Betul Seher; Uzel, Ayse Guzin Taslipinar; Tanriverdi, Burak; Cagil, Nurullah
Highlights: Comparison of the efficacy and safety of the accelerated and the standard CXL in pediatric keratoconus patients. There was no inter-group differences in visual, refractive, topographic and aberrometric results. The accelerated CXL is effective and safe as standard CXL in pediatric keratoconus patients. Abstract: Purpose: To compare the 24 month visual, refractive, topographic and aberrometric results of the accelerated and standard corneal collagen cross-linking (CXL) in pediatric keratoconus patients. Methods: 87 eyes of 64 consecutive keratoconus patients under 18 years old with 24 month follow-up period following standard or accelerated CXL were included. 38 eyes received standard CXL (3 Mw/cm 2, 30 min), while 49 eyes had accelerated CXL (9 mW/cm 2, 10 min). Changes in the uncorrected (UCVA) and best corrected visual acuity (BCVA), spherical equivalent (SE), manifest astigmatism (MA), corneal topographic parameters, and corneal aberrations such as spherical aberration (SA), high order aberrations (HOAs), horizontal and vertical coma were evaluated. Corneal haze was graded and progression rate was assessed. Results: The difference between baseline and 24 months postoperative UCVA, BCVA, SimK (keratometry)-1, SimK-2, Kmax, and the corneal aberrations were not significantly different between the two groups (p > 0.05 for all). The mean reduction in thinnest corneal pachymetry from baseline to 24 months after CXL was higher in accelerated CXL group (p = 0.007). The progression rate was 13.1% in standard and 16.3% in accelerated group (p = 0.754). There were no differences in the grade of corneal haze between the two groups (p = 0.249). No complications were observed in the both groups. Conclusion: The 24 month results of accelerated and standard CXL revealed that, the efficacy and safety of accelerated CXL were the same with standard CXL in pediatric keratoconus patients. As being a rapid procedure, accelerated CXL appears to be more benefical for pediatric patients.